Browsing and believing: divergent effects of internet use on government trust in Central Asia. - Dzutsati, Valery; Rakhmatullayeva, Dinara (Central Asian Survey, 2025)
How does the use of the internet by citizens affect their trust in government and political participation? Previous research has yielded conflicting results. We hypothesize that in authoritarian contexts the passive use of the internet will be associated with lower trust in the government and lower political participation while the active use of the internet will be associated with higher trust in the government and higher political participation. Individuals, who receive the news through the internet, will tend to be sceptical about their governments because they will be exposed to alternative sources of information not controlled by the authoritarian government. The more extensively individuals use the internet for creating content, the more positively they will view the government owing to the effects of the self-selection process of acting under government censorship. Using 11 waves of survey data from four Central Asian countries we test our theoretical conjectures and find support for them.